INTELLECTUAL FREEDOM IN THE UNITED STATES: COMPLEXITIES AND VIOLATIONS IN EDUCATION - SADKI ,Saida; NOUARI, Abdessamed; KAID, Nassima (Faculty of Letters and Foreign Languages Department of English, 2017)
Intellectual Freedom, particularly in education, is one of the most important liberties a nation must preserve in order to achieve development and prosperity. It is largely known that the United States greatly encourages research and knowledge that’s why most people assume that Americans enjoy total and absolute freedom to search in any area and to know about whatever topic they want without the least restriction. Yet, reality proves the opposite. The present work attempts to demonstrate how the Intellectual freedom in the United States is being violated since too long despite the protection that the constitution preserves to it. In this research, we focus on the public schools and libraries where intellectual freedom is restricted either by the federal government, Boards of Education, or students’ parents. We analyze some of these restrictions vis-à-vis the constitution. This will show that the complexity of the Constitution and the ambiguity of the laws which contradict it lead to the constant violation of intellectual freedom. We also show how the American community fights such violations through several organizations and Associations. The discussion of these points will enlighten the readers’ minds and expand their understanding about the real status of the intellectual freedom in the democratic United States.